(untitled) (International Journal of Engineering Management Science, 2024)
This paper presents a comparative analysis of conservation efforts undertaken at three iconic historical monuments in India: the Taj Mahal, Brihadeeswarar Temple, and Khajuraho Group of Monuments. Each case study provides insights into the objectives, scope, methodologies, challenges, and successes of conservation initiatives aimed at preserving these architectural marvels and cultural heritage sites. The first case study focuses on the Taj Mahal, a UNESCO World Heritage Site renowned for its architectural beauty and cultural significance. Conservation efforts for the Taj Mahal involve addressing environmental degradation, structural instability, and tourism pressures while maintaining its historical integrity and aesthetic appeal. The second case study examines the conservation of the Brihadeeswarar Temple in Thanjavur, Tamil Nadu, showcasing the preservation of Dravidian architecture and religious heritage. Conservation strategies for the temple include structural reinforcement, chemical cleaning, and stakeholder engagement to ensure its long-term sustainability. The third case study highlights the conservation challenges faced by the Khajuraho Group of Monuments in Madhya Pradesh, India. Efforts to protect these ancient temples from weathering, biological growth, and visitor impact involve a multidisciplinary approach, including environmental monitoring, stakeholder engagement, and lessons learned from previous conservation projects.